Pengaruh Emotional Quotient Terhadap Strategi Coping Stress Generasi Milenial Dalam Bermedia Sosial - Syafindra, Yaumil; Samputra, Palupi Lindiasari (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The purpose of this study is to find out how emotional quotient influences stress coping strategies in the millennial generation on social media. The method used is synthetic review using journal references for the last ten years. The results of this study indicate that 90% has a positive effect and 10% shows negative results on emotional quotient in coping stress strategies on social media. The conclusion is that there is a positive relationship between emotional quotient and stress coping strategies in the millennial generation which are influenced by different aspects according to what Goleman put forward. Thus, a person's high level of emotional quotient will also affect high coping strategies. The advice given to the millennial generation is expected to be able to manage emotions well and be able to use stress coping strategies in an effort to reduce negative emotions